FLOUTING MAXIMS IN “WHITE HOUSE DOWN“ MOVIE - Sinaga, Rebekka; Handayani, Nurma Dhona (JEE (Journal of English Education), 2020)
Cooperative principles theorized by Grice (1975) explained the way people use the language well and efficiently. There are four maxims in order to have achieve connection during conversation which are maxim of quality, maxim of quantity, maxim of relation, and maxim of manner. The fact is people often not follow and disobey the Cooperative principle and flouts maxim, it is called flouting maxim. The aim of this research was to discuss about the types of maxim which were flouted in the movie "White House Down" written by James Vand Erbilt. As the result, there were 15 data found in the research which flouted, maxim of quantity 4 data, maxim of quality 2 data, maxim of manner 5 data, and 4 data maxim of relation.